Effects of groove configuration and buttering layer on the through-thickness residual stress distribution in dissimilar welds. (August 2021) - Taraphdar, P.K.; Mahapatra, M.M.; Pradhan, A.K.; Singh, P.K.; Sharma, Kamal; Kumar, Suranjit
Abstract: Dissimilar metal welds (DMW) of ferritic to austenitic stainless steel are broadly used in steam generators working in power generation industries. Frequent failure of DMWs from the heat-affected zone (HAZ) of the ferritic part necessitates structural integrity assessment of the DMWs in order to determine and extend the lifetime of these components. In this regard, typical DMWs of SA516–309L–304L and SA516–309L/308L–304L attributed to domestic reactors were fabricated under different welding conditions. The effects of conventional and narrow weld groove configurations, buttering layer, and varying buttering layer width on the through-thickness residual stress fields in the DMWs were investigated experimentally and with the help of numerical simulations. Results show that the narrow groove weld is beneficial in reducing the residual stresses in the weld zone. Incorporating an additional buttering layer in the narrow groove joint further reduced the residual stresses across the weld joint. A 6 mm thick buttering layer was found to be competent enough to minimize the residual stresses dispersed across the weld cross-section. Highlights: Narrow weld groove exhibits reduction in residual stresses in weld zone. Additional buttering layer reduced the level of residual stresses across the weld zone. A 6 mm thick buttering layer was found to be competent enough.